An Overview of Post-Legislative Scrutiny in Western Australia - Sam Hastings; Kate Doust (Jember University Press, 2019)
Twenty years ago, the House of Lords Select Committee into the Constitution focused attention back onto the concept of post-legislative scrutiny. Since then, a clear framework and momentum for systematic post-legislative scrutiny has developed which has enabled parliaments to strengthen their role in the legislative process. However, there is a dearth of academic research into post-legislative scrutiny in Australian jurisdictions. Currently, there is no clear picture of the extent of post-legislative scrutiny in Western Australia and the factors in support, and challenges in implementing, systematic review of legislation. This article examines the extent of post-legislative scrutiny conducted by or overseen by the Parliament of Western Australia. An analysis of review reports and parliamentary debates reveals the outcomes of post-legislative scrutiny by the Executive. This article also examines outcomes of post-legislative scrutiny conducted by parliament through the application of the Westminster Foundation for Democracy’s Principles of Post-Legislative Scrutiny. Finally, barriers to post-legislative scrutiny by the legislature and options for reform are explored.